2014
DOI: 10.1039/c3an01649h
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectroscopic assessment of nanotoxicity in Gram-negative vs. Gram-positive bacteria

Abstract: Vibrational spectroscopy provides a spectral fingerprint identifying the effects of carbonbased nanoparticles in bacterial cells. 3 ABSTRACTNanoparticles appear to induce toxic effects through a variety of mechanisms including generation of reactive oxygen species (ROS), physical contact with the cell membrane and indirect catalysis due to remnants from manufacture. The development and subsequent increasing usage of nanomaterials has highlighted a growing need to characterize and assess the toxicity of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(63 reference statements)
2
16
0
Order By: Relevance
“…Riding et al applied IR spectroscopy to fingerprint microbes following exposure to carbon nanoparticles, and revealed concentration-and size-dependent changes in cellular components 104 . Another study 105 confirmed the ability of IR spectroscopy to characterize changes induced by carbon nanoparticles via investigating their effects in both Gram positive and negative bacteria. Some discriminant biochemical markers, i.e., Amide II and carbohydrate, were picked out to verify the distinct alterations in bacteria with respective cell wall structures.…”
Section: State Of Artmentioning
confidence: 79%
See 1 more Smart Citation
“…Riding et al applied IR spectroscopy to fingerprint microbes following exposure to carbon nanoparticles, and revealed concentration-and size-dependent changes in cellular components 104 . Another study 105 confirmed the ability of IR spectroscopy to characterize changes induced by carbon nanoparticles via investigating their effects in both Gram positive and negative bacteria. Some discriminant biochemical markers, i.e., Amide II and carbohydrate, were picked out to verify the distinct alterations in bacteria with respective cell wall structures.…”
Section: State Of Artmentioning
confidence: 79%
“…Detailed information of the most widely used peak frequencies and their assignments refers to the reviews of IR spectroscopy 108 , Raman spectroscopy 52,87 , and ratios (X cm -1 /Y cm -1 ) 109 . These peaks with remarkable alterations are determined as discriminating biomarkers for diagnosis of changes resulted by specific exposures in many studies 69,87,104,105,108,110 . However, no biospectroscopy-relevant study has yet been found associated with biomarkers for antibiotic 13 resistance of microbiomes.…”
Section: Datasetmentioning
confidence: 99%
“…730785, Sigma-Aldrich, UK) have a 10-nm particle size at a stock concentration of 0.02 mg/mL, dissolved in aqueous buffer with sodium citrate as stabilizer. Two classic soil bacterial strains, Mycobacterium vanbaalenii PYR-1 (Gram-positive) and Pseudomonas fluorescens (Gram-negative), were selected owing to their ubiquity and wide distribution in the soil environment and their well-known physiological behaviour 36,[46][47][48] . These two strains were cultured in Luria-Bertani (LB) broth at 30±2 o C with 150 rpm shaking for 24 h. Bacterial growth was measured every 10 min by optical density at 600 nm (OD 600 ) with a microplate reader (FLUOstar Omega, BMG Labtech, UK).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Specifically, infrared (IR) spectroscopy exploits the principle that biochemical bonds perform some degree of vibrations induced by stretching, bending, scissoring or twisting after energy absorption at particular wavelengths. The "biochemical-cell fingerprint" region is located within the mid-IR region, which is the most information-rich about biochemical structures 36 . Through assessing derived spectral peaks or alterations, i.e., bio-fingerprints, the biochemical structure of interrogated targets can be revealed [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Applying a computational framework to a generated data set allows one to extract distinguishing features associated with altered chemical bonds; these can be associated with constituents such as lipids, proteins or DNA/RNA (24). Raman microspectroscopy has been applied to shed insights into CBN-induced effects (25,26), cell lineage (27) and to generate tissue images (28). …”
Section: Introductionmentioning
confidence: 99%